2015
DOI: 10.3390/rs70506160
|View full text |Cite
|
Sign up to set email alerts
|

Topo-Bathymetric LiDAR for Monitoring River Morphodynamics and Instream Habitats—A Case Study at the Pielach River

Abstract: Airborne LiDAR Bathymetry (ALB) has been rapidly evolving in recent years and now allows fluvial topography to be mapped in high resolution (>20 points/m 2 ) and height accuracy (<10 cm) for both the aquatic and the riparian area. This article presents methods for enhanced modeling and monitoring of instream meso-and microhabitats based on multitemporal data acquisition. This is demonstrated for a near natural reach of the Pielach River, with data acquired from April 2013 to October 2014, covering two flood ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 79 publications
2
113
1
1
Order By: Relevance
“…As stated earlier, the reference water surface model was obtained from the IR water surface returns. The modeled surfaces, in turn, are interpolated from the estimated water level heights along the river axis using the approach described in Mandlburger et al (2015a). Potential tilts of the water surface perpendicular to the flow direction are hereby neglected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated earlier, the reference water surface model was obtained from the IR water surface returns. The modeled surfaces, in turn, are interpolated from the estimated water level heights along the river axis using the approach described in Mandlburger et al (2015a). Potential tilts of the water surface perpendicular to the flow direction are hereby neglected.…”
Section: Resultsmentioning
confidence: 99%
“…Using the semi-automatic approach described in Mandlburger et al (2015a), an approximated Digital Water-level Model (DWM) is first generated based on linear water surface profiles. A refined DWM (50 cm grid) is interpolated from all IR echoes within a small height tolerance band around the approximate model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on task and applied methods, some features are more essential, that must be considered compliting spatial data acquisition. For example, flood-risk maps (Webster et al, 2004) can be generated using DSM, therefore only laser scanning of terrain is sufficient for research, but bathymetric LiDAR (Mandlburge et al, 2015) may be more suitable for river hydrodinamic system modelling and flood simulation. Speaking about object classification and spatial statistics, the research of Jakubowski et al, related with extraction of forest structure metrics, has showed that methods require a threshold density to achieve reasonable accuracy, but that does not benefit significantly from very high LiDAR density (Jakubowski et al, 2013).…”
Section: Figure 4 Knowledge Exchange and Collaboration Among Differementioning
confidence: 99%
“…Data processing experts are mainly associated with digital elevation and surface modeling, which are applied for flood risk and floodplain estimation (Webster et al, 2004), (Casas et al, 2006), (Mandlburge et al, 2015) or road planning . Different experts mention the quality of LiDAR point cloud to generate precise DEMs and DSMs shortly formulating it in high point density (Karel et al, 2006), (Liu et al, 2008), (Zhi and Zhong, 2008).…”
Section: Quality Meaning Among Different Expertsmentioning
confidence: 99%